Nobel Lecture: The Economics of Being Poor - Schultz, Theodore W. (Journal of Political Economy, 1980)
Poor people in low-income countries are no less concerned about improving their lot and that of their children than those of us who have incomparably more income. They are also competent in using their meager resources. Many low-income countries have advanced substantially in recent decades in improving the quality of their population and in acquiring useful knowledge. These achievements imply favorable economic prospects, provided they are not dissipated by politics.